Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi; Wilhelm, René; Schmidt, Wolf Gero (Journal of Computational Chemistry)
Density-functional theory calculations of (TiO2)n clusters (n = 1–5) in the gas phase and adsorbed on pristine graphene as well as graphene quantum dots are presented. The cluster adsorption is found to be dominated by van der Waals forces. The electronic structure and in particular the excitation energies of the bare clusters and the TiO2/graphene composites are found to vary largely in dependence on the size of the respective constituents. This holds in particular for the energy and the spatial localization of the highest occupied and lowest unoccupied molecular orbitals. In addition to a substantial gap narrowing, a pronounced separation of photoexcited electrons and holes is predicted in some instances. This is expected to prolong the lifetime of photoexcited carriers. Altogether, TiO2/graphene composites are predicted to be promising photocatalysts with improved electronic and photocatalytic properties compared to bulk TiO2.

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

Quasiparticle and excitonic effects in the optical response of KNbO3 - Schmidt, Falko; Riefer, Arthur; Schmidt, Wolf Gero; Schindlmayr, Arno; Imlau, Mirco; Dobener, Florian; Mengel, Nils; Chatterjee, Sangam; Sanna, Simone (Physical Review Materials)
The cubic, tetragonal, and orthorhombic phase of potassium niobate (KNbO3) are studied based on density-functional theory. Starting from the relaxed atomic geometries, we analyze the influence of self-energy corrections on the electronic band structure within the GW approximation. We find that quasiparticle shifts widen the direct (indirect) band gap by 1.21 (1.44), 1.58 (1.55), and 1.67 (1.64) eV for the cubic, tetragonal, and orthorhombic phase, respectively. By solving the Bethe-Salpeter equation, we obtain the linear dielectric function with excitonic and local-field effects, which turn out to be essential for good agreement with experimental data. From our results, we extract an exciton binding energy of 0.6, 0.5, and 0.5 eV for the cubic, tetragonal, and orthorhombic phase, respectively. Furthermore, we investigate the nonlinear second-harmonic generation (SHG) both theoretically and experimentally. The frequency-dependent second-order polarization tensor of orthorhombic KNbO3 is measured for incoming photon energies between 1.2 and 1.6 eV. In addition, calculations within the independent-(quasi)particle approximation are performed for the tetragonal and orthorhombic phase. The novel experimental data are in excellent agreement with the quasiparticle calculations and resolve persistent discrepancies between earlier experimental measurements and ab initio results reported in the literature.

Excited-state band mapping and momentum-resolved ultrafast population dynamics in In/Si(111) nanowires investigated with XUV-based time- and angle-resolved photoemission spectroscopy - Nicholson, C. W.; Puppin, M.; Lücke, A.; Gerstmann, Uwe; Krenz, Marvin; Schmidt, Wolf Gero; Rettig, L.; Ernstorfer, R.; Wolf, M. (Physical Review B)

Water Splitting Reaction at Polar Lithium Niobate Surfaces - Dues, Christof; Schmidt, Wolf Gero; Sanna, Simone (ACS Omega)

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Structural dynamics upon photoexcitation-induced charge transfer in a dicopper(i)–disulfide complex - Naumova, Maria; Khakhulin, Dmitry; Rebarz, Mateusz; Rohrmüller, Martin; Dicke, Benjamin; Biednov, Mykola; Britz, Alexander; Espinoza, Shirly; Grimm-Lebsanft, Benjamin; Kloz, Miroslav; Kretzschmar, Norman; Neuba, Adam; et al. (Physical Chemistry Chemical Physics)
A study of structural evolution upon photoinduced charge transfer in a dicopper complex with biologically relevant sulfur coordination.

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, C.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Calculation of spin-spin zero-field splitting within periodic boundary conditions: Towards all-electron accuracy - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)